The Evaluation of Trauma Care: The Comparison of 2 High-Level Pediatric Emergency Departments in the United States and Turkey. Issue 9 (September 2019) - Bal, Alkan; Cooper, Michael; Lee, Amanda; Anil, Murat; Hennes, Halim
Abstract : Objective: The purpose of the study is to compare the outcomes of pediatric trauma patients with motor vehicle crashes (MVCs) and motor vehicle versus pedestrian crashes (MPCs) at a level 1 pediatric trauma center in the United States and a pediatric trauma center in Turkey. Methods: The medical records of all pediatric MVC and MPC subjects presenting to the emergency departments (EDs) of a level 3 hospital in Turkey (Izmir Tepecik Training and Research Hospital [ITTRH]) and a level 1 pediatric trauma center in the United States (Children's Medical Center Dallas [CMCD]) over a 1-year period were reviewed. Data that were collected include patient demographics, prehospital report (mechanism of injury, mode of transportation), injury severity score (ISS), abbreviated injury scale score, Glasgow Coma Scale score, ED length of stay, ED interventions, ED and hospital disposition, and mortality. Patients with moderate (ISS, 5–15) and severe (ISS, >15) trauma scores were included in the study. Results: One hundred six patient charts from the ITTRH and 125 patient charts from the CMCD with moderate and severe ISS due to MVCs and MPCs were reviewed. Most of the patients were pedestrians (86%) in the ITTRH group and passengers (60%) in the CMCD group. The percentage of patients transferred by ambulance (ground or air) to the CMCD and the ITTRH was 97.9% and 85%, respectively. Fifteen percent of ITTRH patients and 2.1% of CMCD patients arrived by private vehicle. Emergency department arrival ISS and Glasgow Coma Scale were similar between the 2 hospitals ( P > 0.05). The overall mortality rate in the study population was 8.8% (11/125) at the CMCD and 4.7% (5/106) at the ITTRH. ( P = 0.223). Blood product utilization was significantly higher in the CMCD group compared with the ITTRH group ( P = 0.005). The use of hypertonic saline/mannitol/hyperventilation in patients with significant head trauma and increased intracranial pressure was higher in the ITTRH group ( P = 0.000). Conclusions: This is the first study that compared pediatric trauma care and outcome at a level 1 pediatric trauma center in the United States and a pediatric hospital in Turkey. Our findings highlight the opportunities to improve pediatric trauma care in Turkey. Specifically, there is a need for national trauma registries, enhanced trauma education, and standardized trauma patient care protocols. In addition, efforts should be directed toward improving prehospital care through better integration within the health care system and physician participation in educating prehospital providers. Data and organized trauma care will be instrumental in system-wide improvement and developing appropriate injury-prevention strategies.